Antibiotic Resistance Pattern of Escherichia coli Derived from Retail Raw Meat in North Sumatera, Indonesia: Antibiotic Resistance Pattern of E. coli obtained from Meat - Rita Rosmala Dewi; Karina Mia Berutu; Juli Mutiara Sihombing (Faculty of Animal Science Universitas Brawijaya, 2023)
Bacteria from animals raised for food that have developed antimicrobial resistance (AMR) may serve as a vehicle for its transmission from animal to human. Nevertheless, the antibiotic resistance profile of Escherichia coli from raw meat is scarcely reported, especially in North Sumatra. The aim of this investigation was to investigate the retail raw meat for the presence of E. coli and its antimicrobial resistance pattern. We purchased 80 packages of fresh meat products from four traditional markets located in Deli Serdang and Medan. Escherichia coli was isolated by an established microbiology test and a phenotypic antimicrobial susceptibility test was conducted by the method of disk diffusion. The data analysis of antibiotic resistance and multi-drug resistance (MDR) levels was performed by using WHONET 5.6. The antibiotic resistance dissimilarity between the two regencies was analyzed by using chi-square analysis. This study observed about 19 E coli isolates (23.7%) were obtained from raw meat. Resistance toward the antibiotics listed as critically important for veterinary and human therapy is increasing concern for public health. The isolates were highly resistant to ampicillin and tetracycline. Meanwhile gentamycin is susceptible. The MDR level of E. coli in both regencies of North Sumatra was about 21.05%. This finding contribute essential information on AMR in food animals and can be used to improve local and regional plans for the administration of antibiotics to livestock.